Joint kinetic determinants of starting block performance in athletic sprinting. Issue 14 (18th July 2018) - Brazil, Adam; Exell, Timothy; Wilson, Cassie; Willwacher, Steffen; Bezodis, Ian N.; Irwin, Gareth
ABSTRACT: The aim of this study was to explore the relationships between lower limb joint kinetics, external force production and starting block performance (normalised average horizontal power, NAHP). Seventeen male sprinters (100 m PB, 10.67 ± 0.32 s) performed maximal block starts from instrumented starting blocks (1000 Hz) whilst 3D kinematics (250 Hz) were also recorded during the block phase. Ankle, knee and hip resultant joint moment and power were calculated at the rear and front leg using inverse dynamics. Average horizontal force applied to the front (r = 0.46) and rear (r = 0.44) block explained 86% of the variance in NAHP. At the joint level, many "very likely" to "almost certain" relationships (r = 0.57 to 0.83) were found between joint kinetic data and the magnitude of horizontal force applied to each block although stepwise multiple regression revealed that 55% of the variance in NAHP was accounted for by rear ankle moment, front hip moment and front knee power. The current study provides novel insight into starting block performance and the relationships between lower limb joint kinetic and external kinetic data that can help inform physical and technical training practices for this skill.